BENTONIT TERMODIFIKASI CETILTRIMETILAMMONIUM SEBAGAI ADSORBEN ION Mn2+ DAN NO3 - , FARIDA NUR SURAIYA, Dr. Sutarno, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Modification of natural bentonite from Thailand by N-cetyl,N,N,N trimethylammonium bromide (CTAB) surfactant for adsorption Mn 2+ and NO3 - in aqueous solution which was activated by 1,5 M H2SO4 has been studied. Modification was done by adding as much as twice of cation exchange capacities (CEC) of surfactant concentration to form a bilayer on external surface of bentonite. Fourier Transform Infrared (FTIR) was used to determine the alteration of functional group and X-ray Diffraction (XRD) was used to characterize minerals composition and crystallinity from adsorbent. The adsorption capacity for Mn 2+ cation and NO3 - anion was analyzed using Atomic Adsorption Spectrometry (AAS) and spectrophotometry UV-Vis with the variation of pH, time and types of adsorbents. The XRD result showed that the major mineral of bentonite was montmorillonite. Activation process of natural bentonite caused dealumination. Adsorption of Mn 2+ and NO 3 - on CTA-bentonite followed Langmuir isotherm. The result showed the adsorption capacity of NO3 - and Mn 2+ on CTA-bentonite was 10.12 x 10 -5 mol/g and 6.56 x 10 -5 mol/g. Energy of adsorption for Mn 2+ and NO3 - was 35.50 kJ/mol and 31.21 kJ/mol, respectively. Meanwhile, adsorption capability of Mn 2+ on natural bentonite > activated bentonite > CTA-bentonite and capability of NO 3 - adsorption showed that CTA-bentonite > activated bentonite > natural bentonite.